In situ growth process and corrosion resistance of a layered double‐hydroxide film on an LA103Z magnesium–lithium alloy. Issue 7 (8th February 2022) - Zhang, Jumei; Duan, Xin; Hou, Anrong; Li, Jiacheng; Lian, Duoduo; Zhang, Mengchun; Wang, Bo
Abstract: A layered double‐hydroxide (Mg–Al LDH) film was grown in situ on an LA103Z magnesium alloy in an aluminum nitrate solution at 90°C by adjusting the hydrothermal reaction time. The Mg–Al LDH film comprised Mg–Al LDH and Mg(OH)2, which was obtained after hydrothermal treatment for 24 h, and was thick and dense, with a uniform and compact LDH sheet growing perpendicular to the surface. The LDH sheet showed the best corrosion resistance, and both the R p and i corr values were two orders of magnitude higher than those of the LA103Z substrate. Nevertheless, the corrosion resistances of the LDH films obtained after treatment for 12 and 30 h were poor owing to the small film thickness and the loose film structure, respectively. Therefore, an appropriate extension of the hydrothermal reaction time can promote the nucleation and growth of LDH and improve the corrosion resistance of the film. When the hydrothermal reaction time exceeded 24 h, the LDH began to dissolve, and the corrosion resistance of the film decreased. Abstract : To reduce the corrosion of the highly active LA103Z Mg–Li alloy, a layered double‐hydroxide (Mg–Al LDHs) film was prepared using the in situ hydrothermal method, and the growth process of the LDH films, and the structure and corrosion resistance of each growth stage were studied. The results showed that the Mg–Al LDH film obtained after hydrothermal treatment for 24 h was thick and dense, which showed the best corrosion resistance.